Carbon Plastics in the Design of Space-Technology Products (Review) - Valueva, M. I.; Evdokimov, A. A.; Klimenko, O. N.; Nacharkina, A. V. (Polymer science. Series D, Glues and sealing materials, 2022)
This review describes the history, current condition, and prospects of the application of polymer-composite materials in the design of space-technology products. Special attention has been paid to the application of materials based on continuous carbon-reinforcing fillers. Russian and foreign sources and patents for inventions are considered. Taking into account global experience, the prospects of designing structures using high-temperature carbon plastics are shown.